COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE IN TELECOMMUNICATION SECTOR COMPANIES - Litha Clara Wattilete (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
This study aims to analyze the financial performance of telecommunication companies listed on the Indonesian stock exchange in 2020-2022, by looking at financial reports using analysis, namely Liquidity Ratios, Solvency Ratios, Activity Ratios, Profitability Ratios. This method uses descriptive and quantitative analysis methods, with a focus on the company's financial performance. The type and source of data used are secondary data in the form of balance reports, income statements and data needed from 2020-2022, the data is taken from reports of telecommunications financial companies published on the Indonesia Stock Exchange. Based on research that can be done is PT .Telkomsel and PT.XL Axiata have better performance. This is evidenced by the good liquidity ratios, solvability ratios, activity ratios, good company profitability ratios every year Keywords: Telecommunication company, Financial Performance, Financial Ratios